The Effect of Contextual Teaching and Learning Approaches on Learning Activities of Students in Science Subjects Subject Matter Changes in Form in Class V Students at School : Pengaruh Pendekatan Contextual Teaching and Learning Terhadap Aktivitas Belajar Siswa Mata Pelajaran IPA Materi Pokok Perubahan Wujud Pada Siswa Kelas V di Sekolah - Moh Bashori Alwy; Nurdyansyah Nurdyansyah (Universitas Muhammadiyah Sidoarjo, 2022)
Contextual Teaching and Learning or better known as (CTL) is a learning approach that is popular today, where an educator in this case the teacher must be able to combine various skills that are expected to make learning run well. Through CTL, it is expected that students can think actively and creatively in their learning activities because learning activities can be realized if students are directly involved in the teaching and learning process, especially in the material of changing objects. Contextual Teaching and Learning approach to learning activities, and student learning outcomes. This research was conducted at MI Miftahul Huda Karang tanjung. In this study using quantitative methods with data collection techniques in the form of questionnaires and observations. The data obtained is managed using SPSS. The results showed that the t-count value in the table was 1.993 while the t-count learning activity was 4.540 so it can be said that (4,540 > 1,993) that Ho was rejected. Thus, CTL affects learning activities and student learning outcomes at MI Miftahul Huda Karang Tanjung